Formation of secondary borides in liquid phase-sintered B6O materials. Issue 7 (June 2016) - Thiele, Maik; Herrmann, Mathias; Müller, Christin; Michaelis, Alexander
Abstract: Liquid phase-sintered B6 O materials with Al2 O3 /Y2 O3 additives were recently developed to yield higher fracture toughness and strength levels than those of pure B6 O-materials. However, the high additive contents of hot-pressed and spark plasma-sintered (FAST/SPS) materials led to the formation of strength-limiting boride precipitates. Systematic variation of the B2 O3 content of the grain boundary phase and thermodynamic calculations carried out in the present work showed that it is possible to avoid boride formation by controlling the decomposition of B2 O3 during densification and adjusting the B2 O3 content of the composition through direct addition of B2 O3 or through reaction of added transition metal oxides such as TiO2 with the starting composition to form B2 O3 .